Using phosphate fertilizer to reduce emitter clogging of drip fertigation systems with high salinity water. (1st June 2020) - Ma, Changjian; Xiao, Yang; Puig-Bargués, Jaume; Shukla, Manoj K.; Tang, Xuelin; Hou, Peng; Li, Yunkai
Abstract: Phosphorous (P) fertigation with high salinity water (HSW) drip irrigation would be an effective measure to relieve soil and water pollution caused by the excessive application of P fertilizer, and achieve synergistic saving of both limited fresh water and non-renewable P resources. However, the emitter clogging issues of drip fertigation systems seriously restricts the utilization of this technology. This study proposes an approach to reduce emitter clogging in HSW drip fertigation systems by choosing the appropriate type and concentration of P fertilizer. The effects of two new types of P fertilizers (ammonium polyphosphate, APP; urea phosphate, UP), and a traditional P fertilizer (monopotassium phosphate, MKP), were assessed at three fertilization concentrations (0, 0.15, and 0.30 g/L) on the clogging behavior of four types flat emitters. The results indicated that the application of MKP aggravated the clogging of emitters in comparison with non-fertilization. While the addition of two new types of P fertilizers (APP and UP) effectively alleviated emitters clogging (the irrigation uniformity of systems increased by 26.2%–74.6%) by inhibiting the formation of carbonate, although precipitation of phosphate, silicate, and quartz increased. Moreover, under the equal application amount of P fertilizer, UP and APP were more effective in relieving clogged when applied at a low-concentration with long-term running and high-concentration with short-term running mode. The results could pave a way for reducing the pollution in agricultural production and conserving freshwater and non-renewable P resources. Highlights: Emitter clogging was assessed in drip fertigation systems high salinity water. The application of UP and APP effectively relieving emitter clogging issues. APP should be applied at a high-concentration with short-term running mode. UP was more effective at a low-concentration with long-term running mode.